HOSPITAL MANAGEMENT INFORMATION SYSTEMS ACCEPTANCE AT WONOSARI REGIONAL HOSPITAL, GUNUNGKIDUL, YOGYAKARTA, INDONESIA - Ahmad Samratul Aula (Epidemiology and Society Health Review (ESHR), 2021)
Background: The hospital management information system (HMIS) is a computer system that processes entire health care business processes, including reporting and administrative procedures, to obtain information quickly, precisely, and accurately. The Wonosari Regional Hospital is a type B hospital that has implemented the HMIS. This study aimed to analyse the HMIS use in the Wonosari Regional Hospital, Gunungkidul, Yogyakarta.Methods: This is a quantitative study using a cross sectional design. Seventy-nine staffs participated in this study that recruited using the purposive sampling technique. Data were collected using a pre-tested questionnaire, then analysed statistically.Results: Perceived ease of use was found significant (p-value â‰¤ 0.05) associated with HMIS use.Conclusions: Perceived ease of use influenced the use of HMIS at the Wonosari Regional Hospital, Gunungkidul, Yogyakarta.